Brain oscillatory activity during motor preparation: effect of directional uncertainty on beta, but not alpha, frequency band - Tzagarakis, Charidimos; West, Sarah; Pellizzer, Giuseppe (Frontiers in Neuroscience, 2015)
In time-constraint activities, such as sports, it is advantageous to be prepared to act even before knowing precisely what action will be needed. Here, we studied the relation between neural oscillations during motor preparation and amount of uncertainty about the direction of the upcoming target. Ten right-handed volunteers participated in a cued center-out task. A brief visual cue identified the region of space in which the target would appear. Three cue sizes were used to vary the amount of information about the direction of the upcoming target. The target appeared at a random location within the region indicated by the cue, and the participants moved a joystick-controlled cursor towards it. Time-frequency analyses showed phasic increases of power in low (delta/theta: <7 Hz) and high (gamma: >30 Hz) frequency-bands in relation to the onset of visual stimuli and of the motor response. More importantly in regard to motor preparation, there was a tonic reduction of power in the alpha (8-12 Hz) and beta (14-30 Hz) bands during the period between cue presentation and target onset. During motor preparation, the main source of change of power of the alpha band was localized over the contralateral sensorimotor region and both parietal cortices, whereas for the beta-band the main source was the contralateral sensorimotor region. During cue presentation, the reduction of power of the alpha-band in the occipital lobe showed a brief differentiation of condition: the wider the visual cue, the more the power of the alpha-band decreased. However during motor preparation, only the power of the beta-band was dependent on directional uncertainty: the less the directional uncertainty, the more the power of the beta-band decreased. In conclusion, the results indicate that the power in the alpha-band is associated briefly with cue size, but is otherwise an undifferentiated indication of neural activation, whereas the power of the beta-band reflects the level of motor preparation.